Evaluation of the differences in perception toward stress and trauma intervention strategies in the South African Police Service - Borien, Jason Dean (University of the Western Cape, 2021)
Magister Commercii (Industrial Psychology) - MCom(IPS) === The current crime rate in the Western Cape plays a crucial role in the exposure of police officers to stressful and traumatic events. The intensity and frequency of this exposure, if not treated, could lead to police officers experiencing comorbid disorders such as post-traumatic stress disorder (PTSD). This leads to an increased need for trauma intervention strategies to be offered, to assist police officers who are exposed to trauma in the South African Police Service (SAPS). Although trauma intervention programmes are established within SAPS, a difference in perception about their effectiveness and service offering are presented. The purpose of this study was to investigate the differences in perception toward stress and trauma intervention strategies within the SAPS in the Western Cape. In order to achieve the purpose of the study, the researcher, tapped into the lived experiences of current police officers and Employee Health and Wellness (EHW) staff, employed by SAPS through semi-structured interviews. Through a comparative design, the study will add value to the current body of knowledge, as differences and similarities between two of the primary role players in the trauma debriefing process within the SAPS are explored. The research sample, recruited by means of convenience sampling, consisted of seven EHW staff members who had experience with dealing with stress and trauma-related programmes, and eight visible policing police officers who had experienced some form of trauma-related incident. The researcher made use of an in-depth interview guide as the research instrument for this study, which consisted of audio-recorded semi-structured interviews with the participants. The audio recordings were transcribed, and then analysed by means of thematic analysis. The findings showed that a difference in perception exists between police officers and EHW staff members toward the effectiveness of trauma intervention strategies offered in the SAPS. The findings also suggest that the majority of police officers do not make use of the trauma intervention programmes in the SAPS, in comparison to EHW staff reporting on good attendance by police officers at the service offerings. Similarities in perception between the two groups presented itself in the form of how trauma is defined, the different responses to trauma and coping mechanisms employed by police officers. The implications of this study include a contribution toward policy and structural amendments of the Employee Assistance Programme (EAP) framework within the SAPS, as well as a motivation for implementing a compulsory trauma counselling programme for police officers.